2023
DOI: 10.3389/fonc.2023.1116648
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and pathological heterogeneity of four common fusion subtypes in Xp11.2 translocation renal cell carcinoma

Abstract: BackgroundXp11.2 translocation renal cell carcinoma (Xp11.2 tRCC) is a group of rare and highly heterogeneous renal cell carcinoma (RCC). The translocation involving TFE3 and different fusion partners lead to overexpression of the chimeric protein. The purpose of this study is to explore the clinicopathological features of Xp11.2 tRCC with four common fusion subtypes.MethodsWe screened out 40 Xp11.2 tRCC patients from January 2007 to August 2021 in our institution. The diagnosis was initially confirmed by TFE3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Xp11.2 translocation RCC with TFE3 gene fusion is a rare subtype of RCC (5). It occurs due to a gene fusion between the TFE3 gene on the Xp11.2 chromosome and one of six different fusion partners (6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Xp11.2 translocation RCC with TFE3 gene fusion is a rare subtype of RCC (5). It occurs due to a gene fusion between the TFE3 gene on the Xp11.2 chromosome and one of six different fusion partners (6).…”
Section: Discussionmentioning
confidence: 99%
“…IHC typically shows minimal reactivity to CK7 or vimentin (31). Overexpression of the TFE3 protein is observed due to translocation, and studies have demonstrated the sensitivity (97.5%) and specificity (99.6%) of TFE3 protein expression in diagnosing Xp11.2 translocation RCC (5,31). Therefore, TFE3 protein expression detected by IHC is the most commonly utilized auxiliary diagnostic technique in clinical practice (32).…”
Section: Discussionmentioning
confidence: 99%
“… 6-8 Notably, different binding partners of TFE3 and TFEB have been associated with distinct clinicopathologic features and clinical behaviors. 9 Given the rarity of this subtype, there is a relative scarcity of research elucidating the molecular drivers of tRCC, resulting in a lack of targeted therapy regimens specific to tRCC.…”
mentioning
confidence: 99%